Fetal and placental size and risk of hypertension in adult life. - Barker, D J (1990)
OBJECTIVE--To study the effect of intrauterine growth and maternal physique on blood pressure in adult life. DESIGN--A follow up study of infants born 50 years previously whose measurements at birth were recorded in detail. SETTING--Preston, Lancashire. SUBJECTS--449 Men and women born in hospital in Preston during 1935-43 and still living in Lancashire. MAIN OUTCOME MEASURES--Placental weight, birth weight, and blood pressure at age 46 to 54 years. RESULTS--In both sexes systolic and diastolic pressures were strongly related to placental weight and birth weight. Mean systolic pressure rose by 15 mm Hg as placental weight increased from less than or equal to 1 lb (0.45 kg) to greater than 1.5 lb and fell by 11 mm Hg as birth weight increased from less than or equal to 5.5 lb to greater than 7.5 lb. These relations were independent so that the highest blood pressures occurred in people who had been small babies with large placentas. Higher body mass index and alcohol consumption were also associated with higher blood pressure, but the relations of placental weight and birth weight to blood pressure and hypertension were independent of these influences. CONCLUSIONS--These findings show for the first time that the intrauterine environment has an important effect on blood pressure and hypertension in adults. The highest blood pressures occurred in men and women who had been small babies with large placentas. Such discordance between placental and fetal size may lead to circulatory adaptation in the fetus, altered arterial structure in the child, and hypertension in the adult. Prevention of hypertension may depend on improving the nutrition and health of mothers.